The E4 allele of the apoE gene acts as a determinant of Metabolic syndrome in men - Vučinić, Nataša S.; Drljača, Jovana; Bačulov, Katarina; Jeremić, Katarina D.; Stojčević Maletić, Jelena; Stokić, Edita (Biologia Serbica, 2019)
Metabolic syndrome (MetS) is a cluster of conditions associated with increased blood pressure, blood sugar levels, excess body fat around the waist, and abnormal cholesterol or triglyceride levels. These conditions occur together, increasing the risk of heart disease, stroke and diabetes. It has been reported that genetic variability at several loci is associated with an increased risk of metabolic syndrome. The human apoE gene, coding apolipoprotein E, has three common polymorphisms in human populations: e2, e3 and e4, which are associated with impaired lipid metabolism. In the present study, apoE gene polymorphism was evaluated in relation to MetS in the male population of Vojvodina. A MetS patient group was examined for apoE variants in relation to biochemical and anthropometric parameters. Total genomic DNA was isolated from blood, and genotyping of apoE polymorphism was determined by PCR-RFLP. Regarding all examined parameters, significantly higher values were detected in men with MetS who were carriers of the e4 allele in their genotype comparing to other allele carriers. A positive correlation was found between the presence of the e4 allele and all measured parameters. These results suggest that the e4 allele may act as a determinant for the development of MetS.